Iterative approach for photonic crystal devices design - Pavel V. Mokshin; Dimitriy L. Golovashkin; Vladimir S. Pavelyev (Физика волновых процессов и радиотехнические системы)
Background. An approach to the design of photonic crystal (PhC) devices is proposed, which differs from the known general-purpose optimization methods (for example, a genetic algorithm or gradient procedures) by using information about diffraction patterns at different frequencies when optimizing an element designed to operate at the selected wavelength. The following is an approach to the design of photonic crystal elements. The proposed approach differs from known general-purpose optimization methods (e.g., genetic algorithm or gradient procedures) by using diffraction pattern information at different frequencies while optimizing an element designed to operate at the selected wavelength. The design of functional PhC structures with expected characteristics (for example, waveguides) for a certain wavelength (albeit given by a monochromatic radiation source) is described. Aim. Development based on the FDTD method and confirmation of the functionality of the iterative procedure for calculating the characteristics of metal-dielectric PhC lattices. Methods. The study is based on an iterative approach to the design of PhC elements based on the use of the FDTD method. Results. Model examples were used for demonstration of practical convergence and applicability of the developed iterative procedure. The efficiency of the PhC waveguide, understood as the ratio of the output energy to the input energy, was increasing at each iteration up to 97.2%. Conclusion. The method of synthesis of metal-dielectric PhC structures with preset properties based on application of developed iterative procedure is proposed and argued. The results of the analysis of the 2D PhC waveguide based on a set of round copper rods show the applicability of the proposed method.